Standardized testing conditions for satellite communications on‐the‐move (SOTM) terminals. (13th August 2018) - Alazab Elkhouly, Mostafa; König, Jonas; Beuster, Niklas; Raschke, Florian; Ihlow, Alexander; Robinson, Colin; Orus‐Perez, Raul; Schurig, Fritz; Knopp, Andreas; Heuberger, Albert; Landmann, Markus; Del Galdo, Giovanni
Summary: Performance validation of Satcom on‐the‐move (SOTM) terminals is becoming more important as the satellite operators continue to recognize the negative influence of suboptimal terminals on their satellite networks. Traditionally, SOTM testing is performed with actual operational satellites in field tests, which lack repeatability. The capability to repeat the conditions in which SOTM terminals are tested is important, especially when the performance of multiple terminals is compared. This contribution describes how the qualification test of SOTM terminals can be conducted in a laboratory environment so that repeatability can be ensured. A major advantage of a laboratory environment is the ability to test the complete terminal as if it was in the field of operation, yet without the involvement of real satellites effectively reducing the costs of testing. The main contributions of this paper are motion and shadowing profiles suitable for standardization of SOTM testing. Standardization of such profiles is necessary to guarantee a fair comparison of the performance of different terminals. Moreover, the paper presents the methodology for testing SOTM terminals at the Fraunhofer Facility for Over‐the‐air Research and Testing, * the procedure used to obtain the proposed profiles and results of testing a Ka‐band SOTM terminal, taken as an example. Abstract : This contribution describes how the qualification test of Satcom on‐the‐move (SOTM) terminals can be conducted in a laboratory environment so that repeatability can be ensured. The main contribution of this paper is the definition of motion and shadowing profiles suitable for standardization of SOTM testing. Standardization of such profiles is necessary to guarantee a fair comparison of different terminals. Moreover, the paper presents the methodology for testing SOTM terminals at the Fraunhofer Facility for Over‐the‐air Research and Testing.